Metrics to understand future maintenance effort required of a complicated source code - Dorin, Michael (2020)
An enduring engineering problem is the creation of a source code too complicated for humans to review and understand. A consequence of a complicated source code is that it requires more effort to be implemented and maintained. Exacerbating the problem is a lack of a proper understanding of exactly what the words “complicated” and “complex” mean, as the definitions of these words are often misconstrued. Some systems are indeed inherently complex, but this does not mean they must be complicated. In our research, several opensource projects were evaluated using software metrics to map the complicatedness of a source code with the ongoing effort to sustain the project. The results of our research show that a relationship exists between a complicated source code and the maintenance effort. It is clear that adhering to proper coding practices and avoiding a complicated code can result in a much more manageable future maintenance effort.